2020
DOI: 10.1111/cob.12411
|View full text |Cite
|
Sign up to set email alerts
|

The effects of adolescent laparoscopic adjustable gastric band and sleeve gastrectomy on markers of bone health and bone turnover

Abstract: Summary 25‐hydroxy vitamin D (25 OHD) deficiency and secondary hyperparathyroidism have been seen after metabolic and bariatric surgery, but data are lacking on the bone health outcomes of adolescent sleeve gastrectomy (SG). The purpose of this study was to examine bone‐related nutrition after SG, compared to laparoscopic adjustable gastric band (LAGB), and trend bone turnover markers following SG. This is an observational study of 197 adolescents who underwent LAGB (n = 98) or SG (n = 99). Bone health labs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
8
2
Order By: Relevance
“…However, adolescents in previous studies undergoing SG report lower PTH and higher 25-hydroxy vitamin D levels than observed in our study ( 24 , 25 ). For instance, Weiner et al reported baseline PTH levels of 42.95 ± 29.37 pg/ml among adolescents with significant decline at 6 (−3.2%) and 12 months (−6.8%) post SG ( 24 ) compared to baseline PTH of 65.9 ± 19.4 pg/ml observed in our study cohort which remained unchanged at 12 months.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…However, adolescents in previous studies undergoing SG report lower PTH and higher 25-hydroxy vitamin D levels than observed in our study ( 24 , 25 ). For instance, Weiner et al reported baseline PTH levels of 42.95 ± 29.37 pg/ml among adolescents with significant decline at 6 (−3.2%) and 12 months (−6.8%) post SG ( 24 ) compared to baseline PTH of 65.9 ± 19.4 pg/ml observed in our study cohort which remained unchanged at 12 months.…”
Section: Discussioncontrasting
confidence: 88%
“…For instance, Weiner et al reported baseline PTH levels of 42.95 ± 29.37 pg/ml among adolescents with significant decline at 6 (−3.2%) and 12 months (−6.8%) post SG (24) compared to baseline PTH of 65.9 ± 19.4 pg/ml observed in our study cohort which remained unchanged at 12 months. Weiner et al also reported a higher baseline 25-hydroxy vitamin D (19.86 ± 8.24 ng/ml) compared to our study (13.6 ± 6.3 ng/ml), although the levels remained unchanged at 12 months in both studies (25). These results are possibly confounded by the fact that patients received vitamin D3 and calcium supplementations, as is typical after bariatric surgery, to counter the detrimental impact on bone health.…”
Section: Discussioncontrasting
confidence: 71%
“…Interestingly, the magnitude of variation in bone turnover markers is reportedly similar between diabetic and non-diabetic cohorts undergoing bariatric surgery, yet patients T2DM patients carry per se a higher risk of osteoporosis ( 122 , 123 ). Because alterations in CTX and P1NP levels have also been reported in adolescents after RYGB ( 124 ) and SG ( 125 ), uncertainties remain on the final effect of bariatric surgery on bone mass peak and subsequent adult risk of osteoporosis.…”
Section: Bone Turnover Markers After Bariatric Surgerymentioning
confidence: 99%
“…The bone resorption marker β-CTX was used for the assessment of bone remodelling in the case presented, mainly for its widespread availability. β-CTX has a wide range of potential applications in paediatric settings regarding either primary or secondary bone metabolism disorders [ 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%